ANALISIS KEPADATAN ARUS LALU LINTAS BERDASARKAN PERSAMAAN LIGHTHILL-WHITHAM-RICHARDS (LWR) (Studi Kasus di Ruas Jalan Raya Krapyak, Semarang) - M.Saifudin Zuhri; kartono kartono (Jurnal Matematika, 2013)
This final paper on mathematical modeling to analyze the traffic on the roadway Krapyak, Semarang equation using Lighthill, Whitham and Richards (LWR), which describes the movement of the traffic flow, the model can be applied to the LWR equation congestion or overcrowding situations more specifically to the junction with one or two roads in and out. The results of dynamics analysis to explain higher density the vehicle speed decreases. The main variables are used to explain the flow of vehicles on a path of motion is flow , velocity , and the density. This problem is analyzed through an implicit scheme and double sweep Cholesky method for determining the density during peak hours. Based on the results of analysis, the highest density occurring on highways Krapyak occurred at 07.00 - 08.00.